EPR-Study of Redox Reactions of Human Placenta Aqueous-Saline Extracts: Storage Temperature and Extraction Time Effects - Repina, S. V.; Nardid, O. A.; Rozanova, E. D.; Tsymbal, L. V.; Schetinsky, M. I.; Naumenko, E. I. (Problems of Cryobiology and Cryomedicine, 2005)
Using EPR method there were investigated redox reactions of stable TEMPON nitroxyl radical with human placenta aqueoussaline extracts depending on placenta tissue storage temperature and extraction time. It was demonstrated, that with an increase in extraction time from 2 to 12 hrs, as well as placenta tissue storage at –20°C for a month, there was a decrease in redox process activity in extracts. Freezing of placenta tissue down to –196°C did not significantly affect redox activity of extracts in comparison with those from native placenta. Investigation results of protein-nucleotide composition in the obtained aqueous-saline extracts testify to the fact, that high-molecular extract fragments possess higher reductive activity in respect of TEMPON.